2006
DOI: 10.1055/s-2006-948292
|View full text |Cite
|
Sign up to set email alerts
|

Genomics of Acute Lung Injury

Abstract: Acute lung injury (ALI) is a complex syndrome involving the interplay of both environmental (such as the addition of mechanical ventilation) and genetic factors. Clinical models have identified risk factors for development and poor outcome but these strategies remain imprecise. To better understand the mechanisms of pathogenesis associated with mechanisms of ALI, candidate genes identified by global expression profiling or related literature searches are being explored for relevant polymorphisms (single base p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 66 publications
(63 reference statements)
0
12
0
Order By: Relevance
“…Prior studies have indicated that genes with increased expression and function variability have longer 39UTRs that are enriched in miRNA-binding sites (35,36). The MYLK gene has a relatively long 39UTR (1,825 base pair), with several splice variants that contribute to the risk and severity of ALI and VILI (4)(5)(6)(7)(8). Because miRNAs regulate a variety of pathophysiological processes, nmMLCK expression may be influenced by ALImodulating miRNAs that bind to the MYLK 39UTR region, consistent with the recognition that multiple inflammatory processes and IL1b-, LPS-, and TNF-a2induced cell activation (macrophages, neutrophils, monocytes, and epithelium) are regulated by specific miRNAs (miR-21, -9, -25, -27b, -100, -140, -142-3p, -181c-, -194, -223, -224, -16, -199a, -155, -146a, -let-7a, -31, 17-3p, and -125b) (37)(38)(39)(40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior studies have indicated that genes with increased expression and function variability have longer 39UTRs that are enriched in miRNA-binding sites (35,36). The MYLK gene has a relatively long 39UTR (1,825 base pair), with several splice variants that contribute to the risk and severity of ALI and VILI (4)(5)(6)(7)(8). Because miRNAs regulate a variety of pathophysiological processes, nmMLCK expression may be influenced by ALImodulating miRNAs that bind to the MYLK 39UTR region, consistent with the recognition that multiple inflammatory processes and IL1b-, LPS-, and TNF-a2induced cell activation (macrophages, neutrophils, monocytes, and epithelium) are regulated by specific miRNAs (miR-21, -9, -25, -27b, -100, -140, -142-3p, -181c-, -194, -223, -224, -16, -199a, -155, -146a, -let-7a, -31, 17-3p, and -125b) (37)(38)(39)(40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…All cyclic stretch (CS) experiments were performed using the FX-4000T Flexcell Tension Plus system (Flexcell International, Hillsborough, NC) equipped with a 25-mm BioFlex loading station designed to provide uniform radial and circumferential strain across a membrane surface along all radii, as described previously (6). Briefly, ECs were seeded at standard densities (8 3 10 5 cells/well) onto collagen type I-coated, flexible-bottomed BioFlex plates transfected with MYLK luciferase reporter and/or miRNA mimics/antagomirs and cultured in EGM-2 complete medium containing 2% FBS at 37 8 C. After 24 hours of culture, the medium was changed in each plate, and confluent EC monolayers were subjected to cyclic stretch (0.5 Hz; 18% linear elongation; 25 cycles/min for 20 min) of desired duration (0-48 h).…”
Section: Cyclic Stretch Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recognize however, that due to sample size and a MAF<20% in this population, our design is underpowered to detect effects in the order of OR∼2.0. Baugh et al 50 also showed in reporter assays that the CATT (5)(6)(7)(8) microsatellite, located in the promoter of MIF gene and in linkage disequilibrium with rs755622, determined the activity of the promoter by the number of repeats. Contrary to these studies, our major findings are focused on the 3′UTR region of the gene, and do not involve individual SNPs but rather involve haplotypes, a finding that is not surprising given the greater power of haplotype analyses.…”
Section: Discussionmentioning
confidence: 99%